The Effect of Estafet Writing to Improve Students‘ Writing Descriptive Text at Senior High School - Kartikasari, Intan; Sudar, Sudar; Basuki, Basuki; Ngafif, Abdul; Rokhayati, Titi (Scripta : English Department Journal, 2023)
The purpose of this study is to determine whether or not using estafet writing to increase students’ ability to write descriptive text in the academic year 2022/2023 is successful in the tenth grade at SMA N 8 Purworejo. The Experimental Group is designated as X-5, and the Control Group is designated as X-6. Prior to starting the treatment, the study’s researcher gave a pre-test to each group. The experimental class’s post-test had a mean score of 61.81. The post-test mean for the control class was 66.11 at the same time. From the calculation of test, It demonstrates that (0.052>0.05) Z-value is greater than Z-table so the test results of hypothesis is the null hypothesis (Ho) is accepted. According to the aforementioned information, using the estafet writing approach to enhance students’ ability to write descriptive prose during the school year 2022–2023, the tenth grade at SMA N 8 Purworejo is ineffective.